MACHIAVELLIANISM AND IMPRESSION MANAGEMENT BEHAVIOR: INTERACTIVE ROLE OF TRAIT ACTIVATING SITUATIONAL MECHANISM - Zahur , Hafsah; Fatima , Tasneem; Raja, Usman (International Journal of Psychosocial Rehabilitation, 2020)
There is a need to develop the understanding of the functional aspects of Machiavellianism with respect to them in-role behavior tendency at work. Therefore, the current study is not only focusing on the direct association of dark trait and behavior outcome but it also investigates the situational mechanism for predicting such associations. This study extends the TAT (Trait Activation Theory) by investigating the direct association of Machiavellianism with impression management and the moderating role of situational mechanism i.e. role ambiguity in predicting the Machiavellianism and in-role impression management behavior outcome by using the field sample of (N=420) employees working in higher education institutes. The results revealed that role ambiguity is a significant situational mechanism to activate the positive attributes of Machiavellian personality trait for predicting self-presentable behavior. It is also proved that Machiavellianism personality has a significant positive association with managing their soft impressions